Pengaruh Daya Serap Air Terhadap Porositas Dan Densitas Komposit Hdroksipatit Berpori Dan Selulosa Nata De Coco - Silvia Anitasari; Yetty Octavia Hutahaean; Abdul Mu’ti (JURNAL KIMIA MULAWARMAN, 2022)
The material that used to bone replacement is much needed. In the beginning, the material of bone replacement came from human or animal bones, but now, the development of synthetic materials as the bone replacement from natural materials increase very fast. The Aim of this study was synthesizing bone graft composite derived from hydroxyapatite and cellulose of nata de coco (HAP/cellulose nata de coco) which tested porosity, density, and water absorption and we expected the porosity, density, and water of the composite were approaching to human or animal bones. Based on statistical analysis by Kruskal Walis (p <0,05) and AUC showed HAp/cellulose of nata de coco with 25 hours precipitation time having bony-like human porosity and there were correlation between porosity and density with water absorption capacity of HAp / cellulose nata de coco our by linear correlation statistical analysis. Keywords: Hydroxyapatite, Cellulose nata de coco, Porosity, Density, Water absorption